Митне регулювання продовольчих товарів - Ушева, Софія Олександрівна; Usheva, Sofiya Oleksandrivna (Ірпінь, 2024)
Робота досліджує теоретико-наукові засади митного регулювання, аналізує митне регулювання продовольчих товарів та виокремлює напрямки удосконалення цього регулювання з урахуванням зарубіжного досвіду

The objectives of the research is to study the theoretical and scientific foundations of custom regulation, analysis of customs regulation of food products and to identify directions for improvement of this regulation, taking into account foreign experience
Customs regulation of food products
Keywords: митні процедури; продовольчі товари; регулювання; customs procedures; food products; regulation